Modulation of Quorum Sensing in a Gram‐Positive Pathogen by Linear Molecularly Imprinted Polymers with Anti‐infective Properties. Issue 52 (1st December 2017) - Motib, Anfal; Guerreiro, Antonio; Al‐Bayati, Firas; Piletska, Elena; Manzoor, Irfan; Shafeeq, Sulman; Kadam, Anagha; Kuipers, Oscar; Hiller, Luisa; Cowen, Todd; Piletsky, Sergey; Andrew, Peter W.; et al.
Abstract: We describe the development, characterization, and biological testing of a new type of linear molecularly imprinted polymer (LMIP) designed to act as an anti‐infective by blocking the quorum sensing (QS) mechanism and so abrogating the virulence of the pathogen Streptococcus pneumoniae . The LMIP is prepared (polymerized) in presence of a template molecule, but unlike in traditional molecular imprinting approaches, no cross‐linker is used. This results in soluble low‐molecular‐weight oligomers that can act as a therapeutic agent in vitro and in vivo. The LMIP was characterized by mass spectrometry to determine its monomer composition. Fragments identified were then aligned along the peptide template by computer modeling to predict the possible monomer sequence of the LMIP. These findings provide a proof of principle that LMIPs can be used to block QS, thus setting the stage for the development of LMIPs a novel drug‐discovery platform and class of materials to target Gram‐positive pathogens. Abstract : Lay it on the line : A linear molecularly imprinted polymer prepared against a signalling peptide of the pathogen Streptococcus pneumoniae can block quorum sensing and abrogate virulence. These results indicate that this approach has the potential to be used for the development of effective anti‐infective agents against pathogenic Gram‐positive bacteria.